Analysis of the Evolutionary Game of Key Participants’ Behavior in the New Energy Vehicle Market - Wu, Hongyue; Huang, Baichong (International Journal of Global Economics and Management, 2024)
This study aims to explore the strategic choices and evolutionary patterns of consumers, enterprises, and governments at different stages of the market development for NEVs (NEVs) by constructing an evolutionary game model involving these three key players. The goal is to provide a theoretical basis and policy recommendations for the healthy development of the NEV market. To address these issues, this research constructs a tripartite evolutionary game model to analyze the behavioral strategies and evolutionary patterns of governments, enterprises, and consumers in the NEV market. Firstly, it is assumed that there is information asymmetry among the three participants in the NEV market, and that all are bounded rationality groups. The participants’ strategic choices will gradually evolve toward the optimal strategy. Based on this, a game model of the three participants—enterprises, consumers, and governments—was constructed, and different market environments were set to simulate the utility and dynamic changes of each participant under different strategies. The results show that in the initial stage, strong government incentive policies can effectively promote the initial development of the market, despite the low acceptance of NEVs by enterprises and consumers. In the development stage, with continuous policy support and the gradual maturation of the market environment, enterprises begin to shift towards NEV production, although consumer acceptance of NEVs still needs improvement. In the mature stage, with the maturity of product technology and the improvement of the market ecosystem, the behaviors of consumers and enterprises become stable, and the NEV market gradually enters a period of steady growth. Through this research, we hope to reveal the mechanism of government policy on market development, identify the optimal incentive measures, improve enterprises’ technological innovation capabilities, and enhance consumers’ purchase confidence, thereby jointly promoting the healthy and sustainable development of the NEV market. With concerted efforts, the NEV market can play a greater role in the construction of a green economy, achieving a win-win situation for both economic and environmental benefits.